IMPROVEMENT OF METHODS FOR ESTIMATING THE LABOR INTENSITY AND DEVELOPMENT TIME OF IT PROJECTS - KRAVCHUK, OLGA; KRAVCHUK, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article focuses on the review and analysis of computer science and information technology as the foundations of modern programming, and the article presents theoretical aspects and concepts of their development that have a significant impact on technological progress and social development, which, in turn, contribute to innovations in various fields, from medicine to finance, making life easier and improving working conditions, creating new business sectors and labor markets that meet the requirements of the digital economy, changing the way of communication, education and interaction in society, including h The article analyzes software, which plays an important role in modern life, helping to solve various tasks and facilitating daily activities of users in various spheres of life. Accordingly, understanding its role and diversity is key to the effective use of technology in the modern world. In this article, we use the concept of logic in programming: decision-making (logic allows programs to make decisions based on conditions and circumstances), error avoidance (logical programming helps to avoid errors and wrong decisions in programs); code efficiency (the use of conditional statements and logical operations helps to make the code more efficient and readable); algorithms (developing effective algorithms requires logical thinking and the ability to make the right decisions at every step). In this article, we have also provided examples of programming languages. A programming language is a formal language construct designed to write computer programs. It defines the syntax and semantics that programmers use to create programs and interact with a computer. Today, there are many different programming languages, each of which has its own features and purpose. This article describes some of the most popular programming languages. Informatics and information technology have become not only the basis of modern programming, but also key determinants of technological progress and social development. Understanding their role and interconnection helps to unlock the potential of these industries for further development and achievement of new heights in technology and innovation.